INDICES OF PATIENTS’ SATISFACTION WITH HEALTHCARE SERVICES IN A TEACHING HOSPITAL - Iddrisu, M. T.; Mumuni, A. N.; Ahmed, A.; Mohammed, A. K.; Yahaya, W. (UDS International Journal of Development, 2019)
Patient satisfaction is an important health service policy tool and an indicator for measuring the quality of health care. Services received by clients or patients from various departments of a hospital undoubtedly contribute to the overall satisfaction rating they may give about that hospital. This study was conducted to assess patients’ satisfaction about services offered by four selected departments of the Tamale Teaching Hospital (TTH) in Northern Ghana. Two hundred (200) in-patients were randomly selected from these four departments, and data was collected from them using a structured questionnaire. Data was analysed by descriptive statistical methods; associations between qualitative variables were explored using Chi-squared cross-tabulation. The results showed that majority (80%) of the patients said they were satisfied with the quality of services they received at the hospital. Patients’ satisfaction was found to be influenced by good communication skills (56%), good attitude (64.5%), availability of nurses (59%), and being made aware of their diagnosis prior to interventions (44.5%). Administrative lapses such as prolonged waiting times (over 1 hour) to access folder (54%) and delays (by additional 30 minutes or more) before seeing a doctor (60.5%) negatively impacted on satisfaction of patients. The level of education of patients had no link with their satisfaction (p = 0.60), but appeared to be associated with knowledge of their rights as patients (p < 0.01). Generally, patients’ satisfaction was based on how they were treated by hospital staff in both outpatient and medical departments. The study therefore recommends proactive measures from the authorities of the hospital towards addressing the identified lapses in order to improve satisfaction of patients. Keywords: Nursing care, Healthcare, Patient satisfaction, Tamale Teaching Hospital, Ghana